PENINGKATAN KOMPETENSI KOGNITIF MAHASISWA BIOLOGI DALAM MATAKULIAH EVOLUSI MELALUI BUKU AJAR BERBASIS METAKOGNISI - Arsih, Fitri; Helendra, Helendra; Fadilah, Muhyiatul (Sainstek : Jurnal Sains dan Teknologi, 2016)
This study aims to improve the cognitive competence of students majoring in biology University of Padang in the course of evolution melalaui use metacognition-based textbook evolution. This research is a class act that is performed in 2 cycles. Subjects in this study were students of biology education courses that take the course of evolution in the second semester of the 2015/2016 academic year. Research instrument used in the form of a booklet role in testing the cognitive competencies. From this research it is known that metacognition-based textbooks can improve cognitive competencies of students, the first cycle of the average cognitive competencies 75.46 with the percentage of achievement criteria of completeness 59.37% increase in cycle 2 with an average of 77.72 with cognitive competencies percentage achieved 81.25% completeness criteria. It can be concluded that through the use of metacognition-based textbook evolution can improve cognitive competence of students.Key words; Compettence, conitive, metaconitive